ANALYZING THE RELATIONSHIP BETWEEN PRODUCT BUYING BEHAVIOR AND INDIVIDUAL SALARY: A CLASSIFICATION AND REGRESSION ANALYSIS - Singh, Rajendra; Singh, Raghvendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper investigates the correlation between individual salary levels and product buying behavior through a comprehensive analysis employing both classification and regression techniques. The study aims to discern patterns and predict future buying behavior based on the income of consumers. In the classification analysis, various demographic and socio-economic factors are utilized to classify individuals into different income brackets. This step enables the segmentation of the population based on their salary levels, facilitating a deeper understanding of the relationship between income and buying preferences. Following the classification analysis, regression techniques are employed to quantify the impact of salary on specific buying behaviors. By analyzing historical data on product purchases across different income groups, regression models are developed to predict the purchasing patterns associated with varying salary levels. This predictive capability enables businesses to tailor their marketing strategies and product offerings to different income segments more effectively.